Penerapan Metode Neighborhood-Averaging Filters (Digital Screen) Dalam Peningkatan Kualitas Pada Citra Dirgantara - Ernida Ernida (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
In this study discusses the noise that exists in aerospace imagery. With this noise, the aerospace image is less than optimal and makes it difficult in the process of retrieving information on the image affected by noise. To eliminate noise can be done using the Neighborhood-Averanging Filters method. Neighborhood-Averanging Filters is one type of lowpass filters that works by replacing the value of a pixel in the image with the mean value (average). By doing a Neighboorhood-Averaging process it is expected to eliminate noise. The benefits of writing this research is to increase knowledge about improving the quality of aerospace imagery. The author can find out whether the Neighborhood Averaging Filters method can improve the quality of aerospace cirta. Simplify solving the problem of improving aerospace image quality so that it gets better results.